2014
DOI: 10.1186/1749-799x-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Do refinements to original designs improve outcome of total knee replacement? A retrospective cohort study

Abstract: BackgroundLong-term results of the 'classic’ low contact stress (LCS) total knee replacement (TKR) have been satisfactory; nonetheless, design changes have been made which resulted in the 'complete’ LCS TKR. The aim of this study is to compare the 5-year incidence of revision and midterm clinical performance before and after introduction of the 'complete’.MethodsA retrospective cohort analysis was conducted on 100 primary uncemented TKRs of both designs. At 5-year follow-up, revision and reoperation rates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The reasons for reoperation after TKA included polyethylene wear, prosthesis loosening, periprosthetic infection, mal-alignment, instability, arthrofibrosis, and periprosthetic fracture [ 33 , 34 ]. In our meta-analysis, no significant difference was observed in the incidence of reoperation between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for reoperation after TKA included polyethylene wear, prosthesis loosening, periprosthetic infection, mal-alignment, instability, arthrofibrosis, and periprosthetic fracture [ 33 , 34 ]. In our meta-analysis, no significant difference was observed in the incidence of reoperation between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The main objectives of TKA are reduction of pain, improvement of function and correction of deformities 15 . Many studies have shown clearly that these objectives are mostly fulfilled following properly performed TKA [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there is no ideal rating system. However, all systems include measurement of pain severity, evaluation of function and assessment of the range of motion 16,18,19 . In our study, we have used these three assessment tools for evaluating patient's outcome postoperatively and preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the differences between the groups were not even close to the recently described minimally clinically important difference [30]. On the other hand, one small study showed that refining a well performing knee design did not influence the functional outcome [31] . In contrast to this finding, a new design was reported to improve the OKS score of TKR patients in a cross-sectional setting [32].…”
Section: Introductionmentioning
confidence: 81%